Left ventricular global longitudinal strain reduction in patients with melanoma and extra-cardiac immune-related adverse events during immune checkpoint inhibitor therapy. (25th November 2020) - Mincu, R.I; Pohl, J; Mrotzek, S; Michel, L; Hinrichs, L; Lampe, L; Rassaf, T; Totzeck, M
Abstract: Background: Immune checkpoint inhibitors (ICI) have tremendously improved survival in patients with melanoma. By unbalancing the immune system, ICI also generate immune-related adverse events (IRAEs) that could affect any tissue, including the heart. Early detection of IRAEs is essential to avoid life-threatening adverse events like myocarditis and to maintain patients under this effective therapy. Aim: To identify whether patients treated with ICI that develop extra-cardiac IRAEs additionally show a subclinical impairment of the heart function. Methods: We have analysed the patients with melanoma without established cardiac disease evaluated in our cardio-oncology unit between July 2018 and December 2019. Data was collected at two timepoints: before initiating the ICI therapy (baseline) and one month after ICI treatment begin (follow-up). Evaluation was performed using clinical data, laboratory parameter including biomarkers, electrocardiography, comprehensive 2D, 3D, tissue Doppler, and speckle tracking echocardiography assessment, and cardiac magnetic imaging. Results: A total of 69 patients with melanoma (59±12 years old, 63% males, 93.8% metastatic disease), without known cardiovascular disease were included. Patients were divided in two groups: patients with extra-cardiac IRAEs (Group 1, n=22) and without IRAEs (Group 2, n=46) after one month of ICI therapy. One patient was diagnosed with immune-related myocarditis at follow-up and was excluded from the analysis. Patients in Group 1 developed colitis (n=10), thyroiditis/hypophysitis (n=8), hepatitis (n=2), and pneumonitis (n=2). There were no differences in age, gender distribution, cardiovascular risk factors, or proportion of metastatic disease between the two groups. The proportion of patients treated with combination ICI therapy (nivolumab plus ipilimumab) was significantly higher in Group 1 (72% vs. 33%, p=0.04). The left ventricular systolic and diastolic function were similar at baseline and after one month of therapy between the two groups, except for the global longitudinal strain (GLS), which showed a significant reduction at follow-up for patients in Group 1 vs. Group 2 (−18.8±2.6% vs. −21±1.2%, p=0.03). The radial and circumferential strain were similar. Follow-up GLS had a good correlation with the extra-cardiac IRAEs rate (r=0.43; p=0.03). Patients with combination ICI therapy had a 5 times higher risk to develop extra-cardiac IRAEs (OR 5.33, 95% CI (1.07–26.61), p=0.04). Troponin and NT-proBNP were not significantly different at follow-up between the two groups. Conclusion: The abnormal function of the immune system triggered by ICI therapy in patients with extra-cardiac IRAEs seems to induce a subclinical left ventricular dysfunction, signalized by a reduction of the GLS. However, the diagnosis criteria for myocarditis were fulfilled in only one patient. The mechanism of these changes should be further investigated and addressed. Funding Acknowledgement: Type of funding source: None